SIMULASI PENGENDALIAN PENCAMPURAN TANGKI MENGUNAKAN METODE ROUTH-HURWITZ DENGAN MATLAB - Dody Wahjudi (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2010)
AbstractÂ Automation control has significant role in human life, specifically for science and industry. Numerous modern applications are the rockets fire, space plane, robot and many others used system control principle. Control systems are necessary in industry operation, examples temperature control in tank, humidity air control in a room, and concentration control in mixing tank.Â The principal process to produce a drink tea is mixing between sugar water and tea water. Level tea at mixture water must be controlled (stable) to have tea concentration equal value in each product. This sensor to monitor output concentration and the information is used to produce error signal. Routh-hurwitz criterion and bode plot are used to get system stability information, while root locus method used to design compensator. The result of shows that the function of PID and lag-lead compensator are improving transient response and steady-state error. The function of lead compensator and PD are improving transient response, while the function of lag compensator and PI are improving steady-state error. Engineer can used compensator to make system have performs and steady state error appropriate with his specification.Â Keyword : routh-hurwitz, bode plot, root locus, compensator.